EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) TERHADAP TEKNIK DASAR DRIBBLING - Lavi Yasir (Journal of Physical Education and Sport Science, 2021)
This study aims to improve the basketball dribbling ability of the men's basketball extracurricular participants at SMPN 1 Garawangi through the TGT training method. This research is an experimental study which was carried out for approximately two months, with the intensity of meeting three times a week. In total there are 6 weeks with a frequency of exercise 3 times in 1 week. Data were collected through pretest and posttest. The data were analyzed using SPSS version 23. The results showed that the TGT training method was very suitable to be applied to men's basketball extracurricular participants at SMPN 1 Garawangi because with the TGT training program extracurricular participants could improve their dribbling abilities. The conclusion is that TGT can improve the dribbling ability of basketball extracurricular participants.